The effectiveness of Lombok traditional games on increasing physical literacy of elementary school - Sudarwo, Raden; Kurniawan, Edi; Irmansyah, Johan; Mujriah, Mujriah; Esse, Balkis Ratu NL (Universitas Negeri Yogyakarta, 2023)
Physical literacy has four components, one of which is the physical component. Increasing the physical component requires learning strategies implemented through physical education, one of which is the traditional Lombok game, which is an effective learning process for children. This research aims to test the effectiveness of traditional Lombok games in increasing physical literacy in elementary school students. This study used the Quasi Experimental Design research method (pretest and posttest control group design) involving 66 class IV students. It consists of two groups, namely, the control group and the intervention group. The intervention group (n = 33; 50% boys and girls) received a weekly 60-minute Lombok traditional game session provided by a local instructor trained in child care, whereas the control group (n = 33; 50% boys and women) received no additional treatment.Components of children's physical literacy were assessed using the PLAYbasic instrument before and after treatment. The results of the PL assessment of the pre-test control group were 42.7 in the Emarging category, the post-test was 45.5 in the Emarging category, while in the experimental group the pre-test was 45.6 in the Emarging category and the post-test was 65.1 in the Competent category, there was an increase in the experimental group. The experimental group using traditional Lombok games had a better level of physical literacy or the Competent category than the control group. While the results of data analysis from the study showed the output of the Independent Samples Test, the Sig value was obtained. (2-tailed) = 0.000 < 0.05.Thus, the traditional Lombok games for grade IV students aged 9 years have a significant influence. Based on these results, it shows the importance of traditional Lombok game interventions that can provide benefits for developing and increasing appropriate physical literacy in later life.